Impulsive consensus of multi-agent systems with stochastically switching topologies. (November 2017) - Zhang, He; Ji, Huihui; Ye, Zhiyong; Senping, Tian; Zhang, Hua; Li, Chenlong
Abstract: In this paper, the impulsive consensus problem for multi-agent systems is investigated. The purpose of this paper is to provide a valid consensus protocol that overcomes the difficulty caused by stochastically switching structures via impulsive control. Some sufficient conditions of almost sure consensus are proposed when the switching structures are the independent process or the Markov process. It is shown that the sum-zero rows of matrix play a key role in achieving group consensus. Furthermore, simulation examples are provided to illustrate and visualize the effectiveness of these results.